2022
DOI: 10.1024/2674-0052/a000012
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with disordered eating and eating disorder symptoms in adolescent elite athletes

Abstract: Abstract. Introduction: Recent studies indicate high prevalences of disordered eating or eating disorders in adult athletes and a worrying increase in adolescent athletes. Although several risk factors for developing eating disorders have been identified for adult athletes (e.g., personality factors, sport-related pressure), research on risk factors in adolescent athletes is scarce. Methods: This study investigates the prevalence of disordered eating and eating disorder symptoms and its association with person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Notably, a recently published systematic review showed that the main factors associated with eating disorders in adolescents are psychological-related variables with a high prevalence of body image dissatisfaction [ 9 ]. In fact, in adolescent elite athletes, a higher prevalence rate for eating pathologies in female athletes, in athletes in high-risk sports, and in those aged between 15 to 18 years has been reported [ 10 ]. It seems that young athletes at greater risk of eating disorders are those pressured to achieve a body composition that optimizes performance; therefore, nutrition–dietetics practitioners should target education regarding the risk factors of eating disorders, nutritional recommendations, psychological well-being, and the relationship to physical performance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a recently published systematic review showed that the main factors associated with eating disorders in adolescents are psychological-related variables with a high prevalence of body image dissatisfaction [ 9 ]. In fact, in adolescent elite athletes, a higher prevalence rate for eating pathologies in female athletes, in athletes in high-risk sports, and in those aged between 15 to 18 years has been reported [ 10 ]. It seems that young athletes at greater risk of eating disorders are those pressured to achieve a body composition that optimizes performance; therefore, nutrition–dietetics practitioners should target education regarding the risk factors of eating disorders, nutritional recommendations, psychological well-being, and the relationship to physical performance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on nutritional patterns and attitudes in gymnasts has focused on athletes practicing WAG or MAG [ 8 , 16 , 27 , 34 ] and RG [ 20 , 59 ]. Only a few authors included in the studied groups gymnasts practicing TG or AG [ 11 , 15 , 17 , 21 , 37 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence shows that practicing gymnastic sports may be a reason for greater susceptibility to risky eating behavior. In gymnastic sports, the emphasis is on thinness, weight control, and sometimes even on weight reduction of athletes, due to performance during competition depending on the subjective opinion of the judges and on aesthetic evaluation, not on measurable results [ 8 , 11 , 23 , 34 ]. The ability to maintain a specific body shape and weight is usually associated with a favorable aesthetic impression and optimization of the exercises performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety [13][14][15][16][17][18][19] Bipolar disorder [20][21][22][23][24] Depression [25][26][27][28][29][30][31][32][33][34][35] Eating Disorders [36][37][38][39][40][41][42][43][44][45][46][47][48] Loneliness [49][50][51][52] Obsessive-Compulsive Disorders [53][54][55] Self-esteem [17,[56][57][58][59] Self-harm [60][61][62] Sleep Problems …”
Section: Mental Health Disorders Elite Athletes Vs Non-athletesmentioning
confidence: 99%